2021
DOI: 10.3389/feduc.2021.566909
|View full text |Cite
|
Sign up to set email alerts
|

The Desire for Social Robots to Support English Language Learners: Exploring Robot Perceptions of Teachers, Parents, and Students

Abstract: Currently there are 4.9 million English Language Learners (ELLs) in the United States, however, only 2% of educators are trained to support these vulnerable students. Educational robots show promise for language acquisition and may provide valuable support for ELLs, yet, little is known about social robots for this population. Inviting participants as cultural informants can ensure that the robot is appropriately designed, situated and adopted into that educational community. Therefore, we conducted an explora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 56 publications
0
4
0
Order By: Relevance
“…To date, very few studies have investigated parents' perceptions on AI-based social robots' usage for language learning (e.g., Lin et al, 2021;Louie et al, 2021;Tolksdorf et al, 2021) and most have used qualitative approaches. Those studies have shown that parents found educational robots to be useful and fun (Smakman et al, 2020) for their children's ESL learning.…”
Section: Ai-based Social Robotsmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, very few studies have investigated parents' perceptions on AI-based social robots' usage for language learning (e.g., Lin et al, 2021;Louie et al, 2021;Tolksdorf et al, 2021) and most have used qualitative approaches. Those studies have shown that parents found educational robots to be useful and fun (Smakman et al, 2020) for their children's ESL learning.…”
Section: Ai-based Social Robotsmentioning
confidence: 99%
“…Third, this study specifically focused on the effect of physical risks on utilitarian and hedonic motivation. Future studies may consider incorporating privacy risk perceptions, which has been identified as an issue of concern for some parents with respect to using robots in children ESL learning contexts (e.g., Louie et al, 2021). Finally, future researchers should attempt to add other factors that may influence utilitarian motivation (e.g., ease of use: Chang et al, 2023) or hedonic motivation (e.g., flow: Zhao & Bacao, 2021), or integrate variables from the Hedonic-Motivation System Adoption Model proposed by Lowry et al (2013), which may produce a better explanation of the variance in parental willingness to adopt AI-based social robots.…”
Section: Limitations and Future Studiesmentioning
confidence: 99%
“…For more detailed information about this study, see ( Björling et al, 2021 ). Having learned from a previous study ( Louie et al, 2021 ) that language learners, their teachers and families preferred the Nao robot form factor, we chose to use the Nao robot for this study. It was also imperative to conduct the study in a real-world setting to better understand how interactions might differ from expectations.…”
Section: Three Research Studiesmentioning
confidence: 99%
“…In this paper, we discuss the rationale for a participatory approach to social robot design. We then present three case studies [two of which have been published in greater detail ( Björling et al, 2021 ; Louie et al, 2021 )] as illustrations of three distinct principles for working with culturally and linguistically diverse children.…”
Section: Introductionmentioning
confidence: 99%